Effectiveness and safety of thoracic segmental spinal anesthesia for breast surgery: A systematic review and meta-analysis - Hamdi, Tasrif; Mastari, Ekawaty S.; Lubis, Andriamuri P.; Ghozali, Imam; Kemalasari, Nadia; Harahap, Awi TM. (Narra J, 2025)
General anesthesia is the standard approach for thoracic and abdominal procedures; however, it has notable limitations, particularly in high-risk patients. Regional anesthesia techniques, such as thoracic segmental spinal anesthesia, have gained popularity due to their potential to reduce these associated risks. The aim of this study was to assess the effectiveness and safety of thoracic segmental spinal anesthesia in breast cancer surgery using systematic review and meta-analysis. This study adhered to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) 2020 guidelines, conducting a comprehensive literature search across ScienceDirect, Cochrane Library, and PubMed databases up to July 4, 2024. The inclusion criteria focused on studies that provided specific information on the effectiveness (postoperative pain reduction) and safety (incidence of adverse events and complications) of thoracic segmental spinal anesthesia, as well as satisfaction among patients and surgeons. Out of 4,060 articles, six studies were included for qualitative assessment, with four further analyzed quantitatively. Meta-analysis findings indicated that thoracic segmental spinal anesthesia provided significantly better pain control at 12 hours postoperatively (SMD: -1.25; 95%CI: -1.54 to -0.96; p<0.0001), although no significant difference was noted at 0 hours (SMD: -1.07; 95%CI: -2.33 to 0.18; p=0.09). Thoracic segmental spinal anesthesia was associated with a lower incidence of postoperative vomiting (RR: 0.46; 95%CI: 0.22–0.95; p=0.04), but it presented a higher risk of hypotension (RR: 2.57; 95%CI: 1.41–4.71; p=0.002). Importantly, no anesthesia-related mortalities were reported. The technique resulted in higher satisfaction levels among both patients (SMD: 0.63; 95%CI: 0.33–0.92; p<0.0001) and surgeons (SMD: 0.81; 95%CI: 0.51–1.11; p<0.0001) compared to general anesthesia. The study highlights that thoracic segmental spinal anesthesia is a safe and effective alternative to general anesthesia for breast cancer surgery, offering superior postoperative pain control, enhanced patient and surgeon satisfaction, and a reduced incidence of postoperative vomiting.